Acidification indices and organic carbon characteristics of acidic soil with different straw incorporation rates - Zhang, Zhifan; Bian, Wenjie; Wan, Jun; Liang, Taibo; Wang, Li; Li, Yi; Ding, Kui; Wu, Bo; Chen, Wenmin; Chen, Yu; et al. (Bangladesh Journal of Botany, 2025)
This study analyzed the acidification indices and organic carbon differences of acidic tobacco-growing soils with different straw incorporation rates. The results showed that the Tengchong acidic tobacco-growing soil had low potential acidity and high base saturation. The long-term straw incorporation increased the organic matter year by year, but the soil pH in the tobacco growing season showed a decreasing trend. The ratio of humic acid to extractable humus (PQ), HA/FA value, E4 value, the rA value at 1630/cm in the infrared emission peak band, and the relative area after integration were significantly higher than those of the soils from Changning Jifei Town and Yongan Xiyang Town. The E4/E6 value, △logK value, and A2920/A1630 value of the soil collected from Tengchong were lower than those of soils from the other two areas. Thus, the soil from Tengchong had a high relative HA content in its humus composition and a complex organic carbon structure. Bangladesh J. Bot. 54(3): 631-644, 2025 (September) Special